Analysis Of Cases Of Disciplinary Violations By Civil Servants In The Department Of Education And Culture Of Medan City (A Case Study At The Department Of Education And Culture Of Medan City) - Majidah Pohan; Ali Yusran Gea; Tamaulina Br. Sembiring (CV. Era Digital Nusantara, 2026)
This study aims to examine the types of disciplinary violations committed by State Civil Apparatus (ASN) within the Medan City Education and Culture Office, identify the factors causing these violations, and analyze the handling mechanisms and corrective measures implemented. The research focuses on the types of disciplinary violations committed by ASN, the internal and external factors influencing these violations, and the disciplinary enforcement process in accordance with statutory provisions. The research method used was empirical research with a field study approach to obtain data directly from relevant agencies. The results showed that civil servant disciplinary violations were still dominated by violations related to attendance, task performance, work ethics, administration, and integrity, with the most frequent violations being unexcused absences, tardiness, and misuse of work time. The causes of violations come from internal factors, such as low work motivation, personal problems, and lack of focus on work, as well as external factors, including a less conducive work environment, perceived unfair treatment, and weak supervision from leaders. Handling of ASN disciplinary violations is carried out based on the provisions of laws and regulations governing ASN as well as Law Number 28 of 1999 concerning the Implementation of a Clean State Free from Corruption, Collusion, and Nepotism, and Law Number 30 of 2014 concerning Government Administration. The handling process includes written summonses, investigations, imposing sanctions according to the level of violation, and granting civil servants the right to pursue administrative action. Efforts to improve discipline are carried out through a combination of coaching, supervision, regulatory dissemination, and the firm application of sanctions, which are expected to enhance the professionalism, discipline, and integrity of civil servants in providing public services.